Problems and prospects of development of the Arctic zone of the Republic of Sakha (Yakutia) - Khoiutanov A. N. (Tendencies and perspectives of social and economic development of Russian regions)
the article examines the current state of the Arctic zone of the Republic of Sakha (Yakutia) and the prospects for its development on the basis of assessing the results of state programs for the development of the Arctic and northern territories of the Republic of Sakha (Yakutia) and identifying problem areas
Keywords: Арктика; Arctic; Арктическая зона Республики Саха (Якутия); развитие арктических и северных территорий; Arctic zone of the Republic of Sakha (Yakutia); the development of the Arctic and northern territories